1996
DOI: 10.1152/ajpregu.1996.270.4.r755
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal expression of adenylyl cyclase subtypes in rat brown adipose tissue

Abstract: The ability of norepinephrine to stimulate adenylyl cyclase (AC) activity increases during the perinatal period in rat brown adipose tissue (BAT), and this increase is associated with changes in the activities of both GS alpha and AC. The purpose of this study was to determine which AC subtypes are present in neonatal BAT and to examine whether the perinatal increase in AC activity corresponds to an increase in the expression of a particular AC subtype. Analysis of AC mRNAs by nuclease protection assay demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Of the nine mammalian AC isoforms identified, three have been shown to be calmodulinsensitive: AC1, -3, and -8 (11). AC1 and -8 are expressed mainly in tissues of the central nervous system, whereas AC3 has a broader profile, having been found in olfactory neuroepithelium (12), testes (13), brown adipose tissue (14), and uterus (15). Our studies demonstrated the presence of a single CaMsensitive adenylyl cyclase isoform in IMCD, namely AC3.…”
mentioning
confidence: 57%
“…Of the nine mammalian AC isoforms identified, three have been shown to be calmodulinsensitive: AC1, -3, and -8 (11). AC1 and -8 are expressed mainly in tissues of the central nervous system, whereas AC3 has a broader profile, having been found in olfactory neuroepithelium (12), testes (13), brown adipose tissue (14), and uterus (15). Our studies demonstrated the presence of a single CaMsensitive adenylyl cyclase isoform in IMCD, namely AC3.…”
mentioning
confidence: 57%
“…The differing results for the effects of 5HT receptor activation on basal AC and on forskolin-stimulated AC thus suggested to us that the unique of effects of the OBX lesion in the older animals reflected alterations in AC itself, either in the isoform being expressed or in the association between AC and G-proteins (Chaudhry et al, 1996;Gao et al, 1998Gao et al, , 1999Scarpace et al, 1996;Zeiders et al, 1999b), which is influenced by factors such as phosphorylation (Premont et al, 1992). This explanation was then verified by assessing the ratio of AC responses to forskolin vs Mn 2 þ , two stimulants that act at different AC epitopes and whose relative activities therefore reflect the AC isoform and the effectiveness of G-protein association with AC (Zeiders et al, 1999b).…”
Section: Figurementioning
confidence: 94%
“…This suggests that, in sensory neurons, the expression of these genes is coordinated and involves tissue-specific transcription factors. AC3 has also been found expressed in many other tissues, including bovine adipose tissue (20,58), male germ cells (35,57), and luteal cells from bovine ovaries (100). Expression of AC3 mRNA has also been detected in human islets isolated from nondiabetic individuals (193).…”
Section: Transcriptional Regulation Of Ac Genesmentioning
confidence: 99%